2015
DOI: 10.1620/tjem.236.175
|View full text |Cite
|
Sign up to set email alerts
|

Early-Onset Graft Pyelonephritis Is Predictive of Long-Term Outcome of Renal Allografts

Abstract: Urinary tract infection (UTI) is the most common bacterial infection encountered in kidney transplant recipients. Graft pyelonephritis (GPN) is associated with acute kidney injury and renal allograft scarring. However, the influence of GPN on renal allograft outcome in kidney transplant recipients remains controversial. Two hundred sixty-five kidney transplant recipients were evaluated for the impact of earlyonset GPN on renal allograft functions between January 2001 and December 2011. Early-onset GPN was defi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 30 publications
(42 reference statements)
1
19
0
Order By: Relevance
“…Total RNA from the FFPE samples were extracted as described previously and reversed‐transcribed into cDNA using SuperScript VILO cDNA synthesis kit (Invitrogen, Carlsbad, CA, USA) (Supplemental Methods).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Total RNA from the FFPE samples were extracted as described previously and reversed‐transcribed into cDNA using SuperScript VILO cDNA synthesis kit (Invitrogen, Carlsbad, CA, USA) (Supplemental Methods).…”
Section: Methodsmentioning
confidence: 99%
“…is a known complication in renal transplant recipients, especially in the early post-transplant period. [1][2][3][4] Differentiating between renal allograft APN and acute rejection (AR) based on clinical symptoms alone can be difficult. The classic tetrad of costovertebral angle tenderness, fever, elevated white blood cell count, positive urine culture used to diagnose acute pyelonephritis in the native kidney, is frequently not useful for renal allografts.…”
Section: Urinary Tract Infection Complicated By Acute Pyelonephritis mentioning
confidence: 99%
See 2 more Smart Citations
“…We previously showed that some patients who successfully underwent RTX developed nocturnal polyuria and nocturia, which affected their QOL [9]. On the other hand, LUT dysfunction may cause urinary tract infection [8], which could affect survival of renal graft [12][13][14]. Thus, we need to focus on LUT dysfunction and LUT symptoms after successful RTX, because it is currently an important issue to improve the QOL of patients with RTX as well as a survival rate of renal graft.…”
Section: Introductionmentioning
confidence: 99%